Knowledge, Network Ties and Improvisation - Legair, Monique (2007)
This study uses the jazz metaphor in an attempt to gain a better understanding of four distinct yet related organizational issues: knowledge development, group formation, characteristics of an effective group and improvisational processes. The aim of this dissertation is to describe and interpret how individual jazz musicians develop and share knowledge within their jazz groups. In order to fully understand the process, the study also investigates how musicians develop relationships with other musicians in order to form a jazz group and the characteristics which must be present if the group is to function effectively to facilitate improvisation during a jazz performance. This study is a phenomenological study which seeks to privilege the experiences of the research subjects through the use of semi-structured interviews, observations, audiovisual data and document analysis to (re)present the research subjectsÃÂÃÂ¢ÃÂÃÂÃÂÃÂ experiences. The main findings are: both explicit and tacit knowledge are equally important in the development of new ideas and in handling the improvisation process; connections to a diverse range of individuals assists jazz musicians in accessing new and creative ideas; and during the improvisation process, individual knowledge is combined with the knowledge of other musicians to create a coherent improvised performance.